TINJAUAN YURIDIS PREDATORY PRICING OLEH PELAKU USAHA RESELLER KARTU PAKET INTERNET DITINJAU DARI UNDANG-UNDANG NO. 5 TAHUN 1999 (STUDI: DI KOMPLEK MMTC JALAN PANCING MEDAN) - Lesson Sihotang; Ricky Omega Yosua (LPPM Universitas HKBP Nommensen, 2020)
Predatory Pricing is the act of a company setting prices below the cost of production in order to eliminate competitors. The study of the law is by predatory pricing by an Internet raffle card in the MMTC complex and section 5 and 8 links to pricing arranged in 1999's statute no. 5 on monopoly and improper business competition. The aim of the study is to find out the adverse effects of the reseller of Internet package Cards and to learn about the pricing of those governed in 1999's statute no. 5 regarding monopoly and unhealthy business competition. This legal research is taken from a normative-empirical legal approach. This approach will merge data that comes from library research and data obtained in the field. Normative data will be generated in legal literature, legal books, legal journals and other materials. While empirical data will be obtained from an interview with the perpetrators of an Internet package card. This legal study will address the indelicate effects of the Internet package card business and the relationships chapters 5 and 8 on pricing under 1999 law no.5. The end of this legal study will be to learn more about the cost of the undergraduate work.